2021
DOI: 10.3390/geosciences11050195
|View full text |Cite
|
Sign up to set email alerts
|

Changes Induced by Self-Burning in Technosols from a Coal Mine Waste Pile: A Hydropedological Approach

Abstract: Coal mining originates environmental impacts on soil and water bodies, including the leaching of Potentially Toxic Elements (PTEs) and Polycyclic Aromatic Hydrocarbons (PAHs) in mine waste piles. This research aims to identify and characterize changes induced by self-burning in Technosols from a coal mine waste pile by means of a comprehensive hydropedological assessment encompassing geochemical, mineralogical, and hydrological data, bearing in mind the potential leaching of PTEs and PAHs. The soil profile fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…2 ). The environmental impact of coal waste depends on several factors, namely, the type, concentration, solubility, mobility, and potential release of chemical elements (Kalembkiewicz and Sitarz-Palczak 2015 ; Espinha Marques et al 2021 ). Some chemical elements are more easily leached and accessible for percolation and mobilization into the environment, namely, Ca, Mg, Na, Mn, Cd, Co, Ni, and Zn (Ribeiro and Flores 2021 ), and all these elements were quantified in high concentrations in the here-presented soil elutriates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 ). The environmental impact of coal waste depends on several factors, namely, the type, concentration, solubility, mobility, and potential release of chemical elements (Kalembkiewicz and Sitarz-Palczak 2015 ; Espinha Marques et al 2021 ). Some chemical elements are more easily leached and accessible for percolation and mobilization into the environment, namely, Ca, Mg, Na, Mn, Cd, Co, Ni, and Zn (Ribeiro and Flores 2021 ), and all these elements were quantified in high concentrations in the here-presented soil elutriates.…”
Section: Resultsmentioning
confidence: 99%
“…Some chemical elements are more easily leached and accessible for percolation and mobilization into the environment, namely, Ca, Mg, Na, Mn, Cd, Co, Ni, and Zn (Ribeiro and Flores 2021 ), and all these elements were quantified in high concentrations in the here-presented soil elutriates. Previous studies in coal mine waste piles (CMW) from the Douro Carboniferous Basin reported different concentrations of leachable elements found in self-burning coal waste samples vs unburned material since the leaching of elements can be temperature-dependent (Espinha Marques et al 2021 ). Querol et al ( 2008 ) reported the leaching potential of unburned and burned coal waste piles and concluded that the burned coal waste produces leachates with higher concentrations of Al, Ca, K, Mg, Mn, and Ni, which corroborates the results presented here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The São Pedro da Cova Coalfield is part of the Douro Carboniferous Basin (DCB), the most important coal-bearing basin in Portugal, and has been, since the early 1990s, the focus of several geological studies with emphasis on tectono-stratigraphic development, e.g., [1][2][3][4][5], paleobotany, e.g., [6][7][8][9][10][11][12], paleozoology, e.g., [6,7,[13][14][15][16], organic petrology and physical parameters of the coals, e.g., [17][18][19][20][21][22][23][24][25], and coal exploration and its environmental impacts (e.g., [26][27][28][29][30][31][32][33][34][35][36]).…”
Section: Introductionmentioning
confidence: 99%